Mechanisms for stable coexistence in an insect community - Meng Fan; Bingbing Zhang; Michael Yi Li (Mathematical Biosciences and Engineering)
In this paper, we formulate a three-speciesecological community model consisting of two aphid species ( Acyrthosiphon pisum and Megoura viciae) and a specialistparasitoid ( Aphidius ervi) that attacks only one of the aphids( A pisum). The model incorporates both density-mediated andtrait-mediated host-parasitoid interactions. Our analysis showsthat the model possesses much richer and more realistic dynamicsthan earlier models. Our theoretical results reveal a new mechanismfor stable coexistence in a three-species community in which anytwo species alone do not co-exist. More specifically, it is known that,when a predator is introducedinto a community of two competing species, if the predator onlypredates on the strong competitor, it can allow the weak competitorto survive, but may drive the strong competitor to extinctionthrough over-exploitation. We show that if the weak competitorinterferes the predation on the strong competitor through trait-mediatedindirect effects,then all three species can stably co-exist.